Association of Neutrophil – to- Lymphocyte ratio as an inflammatory marker in patients with primary Osteoarthritis of the hands - Shna Abdulmajeed Mohammed Amin; Ziad Shafeeq Al-Rawi (Advanced Medical Journal)
Background and objectives: Hand osteoarthritis is a common joint disease that causes pain and functional impairment. Neutrophil to lymphocyte ratio is a novel marker, it can be used for evaluating inflammatory activity in chronic inflammatory disorders. The aim of the study is to evaluate the relationship of neutrophil to lymphocyte ratio in patients with primary osteoarthritis of the hands.